Students' music preferences towards classical music - Mendiković Đukić, Antonella (Array, 2021)
Music preferences can be related to many groups of factors, as LeBlanc’s Interactive theory of music preference suggests. In this research four factors from the model were explored in relation to students’ preference towards classical music: students' age, their gender, their attendance of extracurricular music activities and familiarity of music pieces. Fifteen excerpts of classical music pieces from different musical-historical periods were presented to a sample of 516 students, 7 to 18 years old. Results reveal moderate negative correlation between age and preference towards classical music. Higher preference was found in female students and for familiar pieces. Students that attended extracurricular music activities preferred only some excerpts more. Findings provide strong support to LeBlanc’s model. Implications for teaching are proposed.